Peran Mediasi Minat dalam Pembelian Produk Rabbani: Perspektif Plan of Behaviour Theory - Wulandari, Wahyu; Ariyani, Diyah (IQTISHODUNA, 2024)
This research is motivated by the way women dress that is the cause of sexual harassment. So that the research aims to determine the Effect Analysis of Halal Lifestyle, Price, and Word Of Mouth on Purchase Decisions on Rabbani Products in Salatiga with an Interest as an Intervening Variable. This study used a quantitative method by processing primary data through questionnaires which were distributed to users of Rabbani products in Salatiga as many as 193 respondents using a purposive sampling technique. The analytical tool used in this study is SmartPLS 4.The results of this study indicate that: halal lifestyle, price and word of mouth have a positive and significant effect on purchasing decisions. The interest variable has a positive and significant effect on purchasing decisions. Halal lifestyle, word of mouth has a positive and significant effect on interest. The price variable has a positive and insignificant effect on purchasing decisions. The interest variable can mediate the halal lifestyle variable, word of mouth on purchasing decisions. Interest cannot mediate price on purchasing decisions.